Targeting NR1H/liver X receptor with dendrogenin A differentiates tumor cells to activate a new secretory pathway releasing immunogenic anti-tumor vesicles enriched in LC3-II-associated exosomes. Issue 3 (4th March 2023) - de Medina, Philippe; Bunay, Julio; Poirot, Marc; Record, Michel; Silvente-Poirot, Sandrine
ABSTRACT: Normal cells secrete small extracellular vesicles (sEV), containing exosomes and/or ectosomes, which play a beneficial role in monitoring tissue integrity and immune response, whereas cancer cells constitutively secrete sEV, which contribute to inhibit the immune defenses and promote tumor progression and aggressiveness. Therefore, there is a great interest in reprograming tumor sEV functions toward normal ones. We hypothesized that this could be realized by inducing tumor cell re-differentiation with dendrogenin A (DDA), an endogenous oxysterol and a ligand of NR1 H/LXR (nuclear receptor subfamily 1 group H). At low doses, DDA induces tumor cell differentiation, tumor growth inhibition and immune cell infiltration into tumors. At high doses, DDA induces lethal macroautophagy/autophagy in tumors by increasing LC3 expression at the mRNA and protein level, through NR1H2/LXRβ. In the present study, we showed that low doses of DDA re-differentiate tumor cells by interacting with NR1H2. This results in an increased formation of multivesicular bodies (MVB) in tumor cells and an enhanced secretion of LC3-II-associated exosome-enriched sEV, with immune and anticancer properties. This study highlights the original LC3-II-associated exosome secretory pathway driven by the DDA-NR1H2 complex and paves the way to the development of new therapeutic strategies against pro-tumor exosomes.